The Iconic Brand Love of Batik through Creativity Incubation to Nurul Islami Semarang High School Students - Astuti, Rif’ah Dwi; Setiawan, Andi; Wibowo, Bagus Yunianto; Wahyuni, Sri; Saptianing, Saptianing; Sulistiyani, Endang; Wiedayanti, Destine Fajar; Muhamadin, Norhaslinda bt (Asian Journal of Community Services, 2024)
The potential of Indonesian batik is at risk of being eroded without any preservation and development efforts being made by Indonesian batik craftsmen. This service program identifies a gap in the curriculum and extracurricular content, namely elements of local wisdom and culture that have not been fully adopted by Nurul Islami Unggulan High School. The program implements a creativity incubation approach for Nurul Islami Unggulan High School students so as to strengthen the love of batik as a beloved iconic brand. Furthermore, the objective of this service program is to reinforce character education, which aims to enhance students' knowledge, appreciation, and love for batik. The outcomes of community service are anticipated to serve as a foundation for future service activities.